A new species of the congrid eel genus Bathycongrus (Order Anguilliformes) from eastern Taiwan - Huang, Jian-Fu; Ho, Hsuan-Ching; Chen, Hong-Ming; Chan, Tin-Yam (Zootaxa, 2022)
A new species of the congrid eel genus Bathycongrus is described on the basis of three specimens collected from the deep waters of eastern Taiwan. Bathycongrus melanostomus sp. nov., belongs to the few vertebrae species complex and is distinct in having a short and broad snout; a much reduced caudal fin; abdomen, mouth cavity and gill chamber blackish; small conical blunt teeth on vomer forming an elongate patch; total vertebrae 133–135, and total lateral-line pores 108–109.